PEMBERIAN PUPUK ORGANIK CAIR LIMBAH RUMAH TANGGA DAN BIOSTIMULANT TERHADAP PERTUBUHAN DAN HASIL BROKOLI PADA TANAH PODSOLIK MERAH KUNING - Ananda Eka Putri; Purwaningsih Purwanigsih; Maulidi Maulidi (Fakultas Pertanian, Universitas Janabadra, 2024)
Broccoli (Brassica oleracea, L) is one of the vegetable crops that has the potential to be cultivated in West Kalimantan. This study aims to determine the best interaction of household waste POC and biostimulants on the growth and yield of broccoli on red yellow soil. The research was conducted at Reformasi, Gg. Mathematics, block F, Southeast Pontianak District during August - November 2023. The study used a factorial completely randomized design (CRD) consisting of two treatment factors. The first factor is the concentration of household waste Liquid Organic Fertilizer (LOF) consisting of 3 levels of treatment p1 = 125 ml/l, p2 = 175 ml/l, p3 = 225 ml/l while the second factor is the concentration of biostimulant (B) consisting of 3 levels of treatment b1 = 3 ml/l, b2 = 5 ml/l, b3= 7 ml/l. Each treatment was repeated 3 times with each replicate consisting of 4 sample plants. The variables observed in this study were plant height, number of leaves, plant dry weight, leaf area, flowering age, crop fresh weight and crop diameter. The results showed that the application of household waste LOF with a concentration of 175 ml/l was an effective concentration on the growth variables of broccoli plants while the application of biostimulant with a concentration of 3 ml/l was an effective concentration on the growth and yield variables of broccoli plants in red yellow podzolic soil.